Distribution of carbon stocks in drainage areas on peatlands of Sungai Tohor Village, Meranti Islands District, Indonesia - Sinta Haryati Silviana; BAMBANG HERO SAHARJO; SIGIT SUTIKNO (Society for Indonesian Biodiversity, 2021)
Abstract. Silviana SH, Saharjo BH, Sutikno S. 2021. Distribution of carbon stocks in drainage areas on peatlands of Sungai Tohor Village, Meranti Islands District, Indonesia. Biodiversitas 22: 5106-5114. Peatland ecosystems provide a variety of environmental services and biodiversity with their ability to store and absorb carbon. The increase of land clearing followed by the construction of drainage or canal has resulted in the degradation of peatlands and is prone to fire incidences. Canal construction, whether we realize it or not, has a negative ecological impact on the in situ (local) environment, namely land degradation and subsidence, as well as a wider (global) impact in the form of loss of carbon stocks, increased GHG emissions that can trigger global warming. This study aims to identify the distribution of carbon in the area where drainage is made where the distribution of carbon stock in starting at a distance of 10 m, 50 m, 100 m, 250 m, and 350 m from the canal. The study was conducted on the community plantations including unburned areas (rubber plantations and secondary forests) and burned areas. The influence of land use and drainage development on carbon stock distribution is rarely known. The results showed a decrease in C-Stock with a decrease in drainage distance. The quantity of carbon stock in secondary forests ranged from 13.275 ton ha-1 - 24.839 ton ha-1, Burnt Area-1 ranged from 6.995 ton ha-1 - 11.59 ton ha-1, and Burnt Area 2 ranged from 4.677 ton ha-1 - 12.580 ton ha-1. In contrast, rubber plantations had higher C-stock in the initial observation distance, around 9.064 ton ha-1 - 11.805 ton ha-1, which may be due to intensive land use near the canal.